Evaluation of Academic Detailing Programme on Childhood Diarrhoea Management by Primary Healthcare Providers in Banke District of Nepal (Journal of Health, Population and Nutrition, 2013)
Academic detailing is rarely practised in developing countries. A randomized control trial on healthcare service was conducted to evaluate the impact of academic detailing programme on the adherence of primary healthcare providers in Banke district, Nepal, to childhood diarrhoea treatment guidelines recommended by World Health Organization/United Nations Childrens Fund (WHO/UNICEF). The participants (N=209) were systematically divided into control and intervention groups. Four different academic detailing sessions on childhood diarrhoea management were given to participants in the intervention group. At baseline, 6% of the participants in the control and 8.3% in the intervention group were adhering to the treatment guidelines which significantly (p